2009
DOI: 10.1007/s10802-009-9305-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teacher Cognition and Behavior in Children’s Peer Relations

Abstract: This study explored the role of the classroom teacher in peers' evaluations of liking and disliking of their classmates. Teacher cognitions about children (teacher liking of students, teacher attributions for aggressive student behavior) and teacher behavior toward children (positive, corrective/negative) were examined as mediators in the link between children's own behavior (aggression, prosocial behavior) and peer liking and disliking. Participants were 127 second-graders in 12 classrooms (64 males, 63 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 32 publications
(39 reference statements)
8
76
1
3
Order By: Relevance
“…Whereas children also demonstrated a tendency to rate an actor with a disliked or average reputation more positively after watching him receive praise, the effect was much less pronounced. These findings are similar to those from a recent naturalistic study that found teachers' observed negative/corrective (but not positive) behavior to partially mediate the relationship between child aggression and peer disliking (McAuliffe et al 2009). …”
Section: Influence Of Parental Feedback On Children's Social Statussupporting
confidence: 88%
See 1 more Smart Citation
“…Whereas children also demonstrated a tendency to rate an actor with a disliked or average reputation more positively after watching him receive praise, the effect was much less pronounced. These findings are similar to those from a recent naturalistic study that found teachers' observed negative/corrective (but not positive) behavior to partially mediate the relationship between child aggression and peer disliking (McAuliffe et al 2009). …”
Section: Influence Of Parental Feedback On Children's Social Statussupporting
confidence: 88%
“…First, we note that while we focused here on parent feedback, the comments of other adults, especially teachers, also likely have important associations with peer status (e.g., McAuliffe et al 2009). Second, while the brief playgroup interaction captures peers' impressions of liking and disliking, which may be rapidly influenced by even a single instance of aggression (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Using cross-sectional designs, a teacher's criticism toward second graders in front of peers (McAuliffe, Hubbard, & Romano, 2009) and a teacher's personal disliking of elementary school students (Chang et al, 2007) and middle school students (Chang et al, 2004) mediated the negative relation between student externalizing behaviors and social preference.…”
Section: Externalizing Behavior Problems and Social Preferencementioning
confidence: 99%
“…Special education and elective teachers were not eligible. Study participation was optional, and 35 teachers agreed to be in the study; however, during the course of the research 3 teachers quit their teaching job and 6 additional teachers' data were not used because fewer than 40% of their students gave active consent, a cutoff which has been suggested to obtain valid sociometric nominations (Hughes & Kwok, 2006;McAuliffe et al, 2009). All teachers provided active, written consent.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation